Validation of genetic predictors of late radiation-induced morbidity in prostate cancer patients. (2nd November 2017) - Schack, Line M. H.; Petersen, Stine E.; Nielsen, Steffen; Lundby, Lilly; Høyer, Morten; Bentzen, Lise; Overgaard, Jens; Andreassen, Christian N.; Alsner, Jan
Abstract: Introduction: Normal tissue morbidity sets the dose limit for radiotherapy (RT) in cancer treatment and has importance for quality of life for cancer survivors. A previous study of prostate cancer patients treated with RT generated clinical data for radiation-induced morbidity measured by anorectal physiological methods and validated questionnaires. Other studies have identified genetic predictors associated with late radiation-induced morbidity outcome. We have expanded biobank material aiming to validate single nucleotide polymorphisms (SNPs) and a gene expression classifier with endpoints on patient-reported outcomes and biomechanical properties of the anorectum from our cohort matching originally published endpoints. Materials and methods: The present cohort of prostate cancer patients was treated with RT curative intent in 1999–2007. Nine SNPs associated with late radiation-induced morbidity were tested in 96 patients (rs2788612, rs1800629, rs264663, rs2682585, rs2268363, rs1801516, rs13035033, rs7120482 and rs17779457). A validated gene expression profile predictive of resistance to radiation-induced skin fibrosis was tested in 42 patients. An RT-induced anorectal dysfunction score (RT-ARD) served as a fibrosis-surrogate and a measure of overall radiation-induced morbidity. Results: The lowest p -value found in the genotype analyses was for SNP rs2682585 minor allele ( A ) in the FSHR gene and the RT-ARD score with odds ratios (OR) = 1.76; 95% CI (0.98–3.17) p = .06, which was out of concordance with original data showing a protective effect of the minor allele. The gene expression profile in patients classified as fibrosis-resistant was associated with high RT-ARD scores OR 4.18; 95% CI (1.1–16.6), p = .04 conflicting with the hypothesis that fibrosis-resistant patients would experience lower RT-ARD scores. Conclusions: We aimed to validate nine SNPs and a gene expression classifier in a cohort of prostate cancer patients with unique scoring of radiation-induced morbidity. One significant association was found, pointing to the opposite direction of originally published data. We conclude that the material was not able to validate previously published genetic predictors of radiation-induced morbidity.